Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1172/jci112139
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stimulation of sugar uptake in rat thymocytes. An extranuclear action of 3,5,3'-triiodothyronine.

Abstract: In previous studies we have demonstrated that 3,5,3'-triiodothyronine (T3) in vitro produces a prompt increase in the uptake of the sugar analogue 2-deoxyglucose (2-DG) by freshly isolated rat thymocytes. This effect is prompt, being evident at 20 min after addition of T3, is independent of new protein synthesis, and can be elicited by physiologic concentrations of the hormone. In the present studies, we have sought to determine whether physiologic doses of T3 are capable of inducing an increase in 2-DG uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
(17 reference statements)
2
17
0
Order By: Relevance
“…Glucose uptake in skeletal muscle cells has been well characterized in the last 20 years by several groups (4,5,24,59,61,69). We carried out experiments to confirm our experimental model, measuring glucose uptake in L6 myoblasts induced by 0.1 nM insulin or 10 nM IGF-I ( Fig.…”
Section: Short-term Modulation By Thyroid Hormone Of Basal and Igf-i-mentioning
confidence: 90%
“…Glucose uptake in skeletal muscle cells has been well characterized in the last 20 years by several groups (4,5,24,59,61,69). We carried out experiments to confirm our experimental model, measuring glucose uptake in L6 myoblasts induced by 0.1 nM insulin or 10 nM IGF-I ( Fig.…”
Section: Short-term Modulation By Thyroid Hormone Of Basal and Igf-i-mentioning
confidence: 90%
“…One such possibility is an effect on basolateral membrane potassium conductive pathof T 3 induced a fast, dose-and time-dependent increase in fluid reabsorption [11]. The direct effect of thyroid ways [29]. Indeed it has been demonstrated that, in rat diaphragm and liver cells, single administration of high hormones on tubular transport processes has been confirmed by experiments designed to compare the time doses of T 3 to euthyroid rats increased the potassium permeability of the cell membrane well before a rise in course in changes in GFR, filtered sodium load and specific transport systems: it was found that, after a single Na-K-ATPase activity was observed [30][31][32].…”
Section: Studies On Animalsmentioning
confidence: 99%
“…Segal and Inbar showed 20 years ago that physiological concentrations of T 3 -activated glucose transport in rat thymocytes [14,15,61]. This was a novel effect of thyroid hormone that was extranuclear in mechanism, that is, independent of protein synthesis [61].…”
Section: Contribution Of [Ca 2+ ] I To the Function Of Plasma Membranmentioning
confidence: 99%
“…This was a novel effect of thyroid hormone that was extranuclear in mechanism, that is, independent of protein synthesis [61]. Segal proposed that the effect was mediated by the interaction of thyroid hormone with a putative membrane receptor since cytoplasmic free concentration rose promptly as a consequence of an influx of Ca 2+ from the extracellular medium, and was associated with a calmodulin-mediated activation of adenylate cyclase, increase in cAMP, and increase in activity of the membrane glucose transporter [15].…”
Section: Contribution Of [Ca 2+ ] I To the Function Of Plasma Membranmentioning
confidence: 99%